Perdarahan uterus abnormal - menoragia pada masa remaja - Wantania, John J. E. (Jurnal Biomedik : JBM, 2016)
Abstract: WHO identifies adolescence as a period in human growth and development that occurs after childhood and before adulthood from age 10 to 19 years. Two large studies have shown that a greater increase in BMI in childhood is associated with earlier onset of puberty. In general, the age of menarche ranges relatively stable from 11 to 14 years with a median of 12.43 years. The average of menstrual cycle interval is 32.3 days in the first reproduction year. After that, the interval of menstrual cycles generally ranges from 21 to 45 days. Duration of menstruation is 7 days or less. The use of tampons or pads are generally three to six pieces per day. Abnormal uterine bleeding (AUB) is defined as a significant change in the pattern of menstruation or the volume of blood discharge, and is the most common complaint in women. In early adolescence, 75% of adolescents experience abnormal uterine bleeding. Heavy menstrual bleeding (HMB) as well as heavy and prolonged menstrual bleeding (HPMB) is the preferred term for excessive menstrual bleeding. Medical treatment is performed as the initial treatment as long as there is no contraindication. When the acute bleeding has been handled, it is recommended to arrange a transition in the long-term treatmentKeywords: menstruation, teens, abnormal uterine bleeding (AUB)Abstrak: WHO mengidentifikasi remaja sebagai periode pada pertumbuhan manusia dan perkembangan yang terjadi setelah masa kanak-kanak dan sebelum dewasa, dari umur 10 sampai 19 tahun. Dua studi besar telah membuktikan bahwa peningkatan IMT yang lebih besar pada masa kanak-kanak berhubungan dengan onset pubertas yang lebih awal. Usia menarche umumnya relatif stabil berkisar antara 11 dan 14 tahun dengan median 12,43 tahun. Interval siklus rata-rata ialah 32,3 hari pada tahun reproduksi pertama dan interval siklus mentruasi umumnya 21-45 hari. Lama menstruasi ialah 7 hari atau kurang. Penggunaan tampon atau pembalut umumnya tiga sampai enam buah per hari. Perdarahan uterus abnormal (PUA) adalah perubahan signifikan pada pola atau volume darah menstruasi dan merupakan hal yang paling banyak dikeluhkan oleh wanita. Pada awal usia remaja, 75% remaja mengalami keluhan PUA. Perdarahan haid berat (heavy menstrual bleeding) dan perdarahan haid berat dan memanjang (heavy and prolonged menstrual bleeding) ialah istilah yang lebih sering digunakan untuk perdarahan haid yang berlebihan. Penanganan medis menjadi terapi awal bila tidak ada kontrindikasi. Bila perdarahan akut sudah ditangani, direkomendasikan untuk melakukan transisi pada penanganan jangka panjang.Kata kunci: menstruasi, remaja, perdarahan uterus abnormal (PUA)